Autoethnography, Folklore and National Emancipation: ‘The Temptation of Experience’ in the work of Kata Jajnčerova - Potkonjak, Sanja (Array, 2010)
The paper explores the work of one of the first Croatian women ethnographers, Kata Jajnčerova. Although a women of the previous century and a peasant women of limited education destined to become the first ethnographic sight witness, Kata Jajnčerova stands as a cornerstone in nativistic teleologies of nation formation, as well as a scholarly exemplar of an early self-explanatory “native” ethnographic correspondent. The aim of the paper is to frame the obsessive topics and presumptuous techniques of Jajnčerova’s authority. The paper focuses on the mechanisms by which a native subject wishes for and constructs the emancipation of the folk from the epistemic obliteration by dominant political narratives – both by introducing the idea of voicing the experience and by solidifying a narrative to become a written testimony of the folk. Through the analysis of Kata Janjčerova’s texts the author questions the significance of the ‘temptation of experience’ for the establishment of ‘reliable’ cultural writings on Croatian rural life from the end of the 19th and the beginning of the 20th century. By placing Kata Janjčerova in early Croatian ethnography, in which this unique woman’s text served as a witness of women’s experience of life in a rural community, the author tries to emphasize the context of production of knowledge on nation and culture in which even women’s writings functioned primarily as political negotiators between stronger and weaker historical subjects.